Czech literature in English translation - Soukupová, Dana (2006)
My diploma thesis aims at the Czech literary works translated into English and published in the English-speaking countries, predominately in the United Kingdom and in the United States, and, partly, in the Czech Republic after 1989. I give a brief summary of the development of translating from Czech into English. Then I describe the situation in the field of translations from Czech into English after 1989. I mention both the translators and publishing houses that are involved in the mentioned process